1994
DOI: 10.1177/000331979404500806
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Sialic Acid and Acute-Phase Proteins in Patients with Myocardial Infarction

Abstract: Plasma total sialic acid (TSA) and lipid-associated sialic acid (LASA) were measured in 19 patients with a myocardial infarction (MI) on days 1, 2, and 5 and in 19 normal subjects. On each day plasma TSA was elevated in the MI patients as compared with that of normal subjects, although no significant difference was seen in the plasma LASA between the two groups. The following plasma acute-phase proteins were also assayed in the MI patients and the normal subjects: C-reactive protein (CRP), alpha-1 acid glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 11 publications
(2 reference statements)
1
36
1
Order By: Relevance
“…In addition, we showed that C-reactive protein concentrations in those coronary heart disease patients who suffered from stenoses in the pelvis and leg arteries or the extra-cranial arteries supplying the brain, or from aneurysm of the abdominal aorta, were significantly higher than C-reactive protein concentrations in patients suffering from coronary heart disease alone ( Table 2). The significant elevation of the C-reactive protein level above control in the chronic phase after acute myocardial infarction or in generalized atherosclerosis [12] is small compared with the substantial change in patients with an acute myocardial infarction [7,[28][29][30] (i.e. up to 10-100 fold higher than the values found in normals).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, we showed that C-reactive protein concentrations in those coronary heart disease patients who suffered from stenoses in the pelvis and leg arteries or the extra-cranial arteries supplying the brain, or from aneurysm of the abdominal aorta, were significantly higher than C-reactive protein concentrations in patients suffering from coronary heart disease alone ( Table 2). The significant elevation of the C-reactive protein level above control in the chronic phase after acute myocardial infarction or in generalized atherosclerosis [12] is small compared with the substantial change in patients with an acute myocardial infarction [7,[28][29][30] (i.e. up to 10-100 fold higher than the values found in normals).…”
Section: Discussionmentioning
confidence: 84%
“…up to 10-100 fold higher than the values found in normals). several days after the acute event, C-reactive protein levels return to the control range again [28,31] . The elevation of C-reactive protein in acute myocardial infarction seems to be independent of the underlying atherosclerotic process and may be triggered, for example, by soluble inflammatory factors such as interleukin-1beta and tumour necrosis factor-alpha, which are related to the extent of myocardial necrosis [32] .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, other investigators have confirmed that there is a strong positive association between markers of inflammation (especially CRP) [10,17] , hypercoagulability (i.e. fibrinogen) [18][19][20] and S-TSA. The previous data are in accordance with our findings.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, ALA, which its anti-inflammatory specifications has rarely been searched until today, has been administered to laminectomized rabbits via intramuscular course and effects of the substance on total antioxidant capacity (TAS), total oxidant capacity (TOS), paroxonase (PON), and total sialic acid levels Analysis of sialic acid provides important clues for the diagnosis and estimation of the prognosis of the diseases, and is being used increasingly nova days [17,25] . In our study show that, plasma SA levels of laminectomized animals were higher than the levels of laminectomy + ALA administered, and only ALA administered animal groups.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this fact, evaluation of SA concentration may be an important sign in the diagnosis of inflammatory diseases [19,[21][22][23][24] . Although the mechanism in the increase of serum SA level during the inflammatory conditions is not clear, many investigators indicated the role of AFPs which share the same structure with SA [17,19,20,25] . Since acute phase reactants are glycoprotein in structure, it has been reported that increase in these proteins affects the TSA levels [20] but not reflects the increases in SA levels exactly, which also bears glycoprotein structure [19] .…”
mentioning
confidence: 99%